PENGARUH PENDIDIKAN KESEHATAN BOOKLET DIGITAL TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) DI SMA NEGERI 16 KOTA BATAM - Lusi Yana Br Panjaitan; Septi Maisyaroh Ulina Panggabean; Nuari Andolina (Jurnal Ilmiah Kebidanan Imelda, 2025)
Cancer is a non-communicable disease that causes a worldwide health burden of 13%. Cancer is characterized by abnormal cells that grow uncontrollably of more than 200 types of cancer, breast cancer is the most common. As many as 2.3 million women in the world are diagnosed with breast cancer. Data from the Batam City Health Service in 2023 found 1,169 cases of breast cancer and 22 of them suffered from teenagers aged 15-19 years. Based on an initial survey at SMAN 16 Batam City, it was found that teenagers' knowledge about BSE was still lacking. The aim of the research is to increase teenagers' knowledge through digital health education booklets. Method: Quasi-experimental research type, one group pretest posttest design, sample of 78 respondents, simple random sampling technique. The research instrument used a questionnaire with the Wilcoxon test. Results: Pretest knowledge in the good category was 17.9%, fair was 61.5%, and poor was 20.5%. Posttest knowledge in the good category was 64.1%, sufficient 28.2%, and poor 7.7%. The Wilcoxon test results obtained a p value of 0.000. It is hoped that it can provide education to teenagers as an effort to detect breast cancer early and make BSE a routine habit.